The Delta of Shatt Al-Arab River, Framework and Evolution - Al-Mosawi, Walaa M.; Al-Manssory, F.aiq Y. (Mesopotamian Journal of Marine Sciences, 2019)
Shatt Al-Arab Delta was built at the northern end of the Arabian Gulf (AG) on the top of a longitudinal shallow marine basin shape. Today the hydrologic regime of Shatt Al-Arab River is suffering from many changes caused by anthropogenic activity impacts, led to a significant decrease in water feeding about 1000 m3/sec in 1990 into less than 50m3/sec in 2016. Many previous studies have been discussed as well as performing a marine geophysical surveys to assess the evolution of Shatt Al-Arab Delta during the history. Many phenomenon and progradational parts of the Delta: Prodelta, distributary channel, bay fill, and beach ridge have been identified from marine geophysical survey. The lower reflector is appear as irregular surface, which could indicate the presence of an ancient beach that appear as a terraces region due to fluctuation in the sea level. The second reflector appear as a layer have had variation depth, which may represent a beginning of the ancient delta creation after of the sea level stability (< 5000 years ago). The top layers have been deposited, which represent the present day delta. This present result suggests that there are three phases of delta evolution during history, the first phase represents the beginning of the modern origin of this delta during 1000-2000 yr. ago when the Tigris and Euphrates Rivers are connected together, at that time the delta was not so large and have been formed by the excess sediment that coming from the marshes after the two Rivers dumping most of their sedimentary load there. The second phase represents the activation of this delta with stabilized coastline, especially after the manmade connection between Karun and Shatt Al-Arab Rivers, which occurred before thousand years ago. The third phase represents the last half of the previous century when several factors contributed on the evolution of Shatt Al-Arab delta, including hydrological, climatological and anthropogenic factors.